Factors Associated With Epilepsy in Children With Periventricular Leukomalacia - Humphreys, P; Deonandan, Raywat; Whiting, S; Barrowman, N; Matzinger, MA; Briggs, V; Hurteau, J; Wallace, E (Université d'Ottawa | University of Ottawa, 2007)
Children with cerebral palsy associated with periventricular leukomalacia frequently develop unprovoked epileptic seizures. This article reports an analysis of risk factors for epilepsy in children with radiologically confirmed periventricular leukomalacia. This cohort was screened for epilepsy and for an array of clinical and demographic factors. Of 154 subjects with radiologically confirmed periventricular leukomalacia, 40 (26.0%) had epilepsy. In the epileptic group, radiologic pathology other than periventricular leukomalacia was uncommon. Significant associations were found between epilepsy and cerebral palsy patterns other than spastic diparesis, mental handicap, cortical visual impairment, neonatal seizures, and severe periventricular leukomalacia. Only the presence of neonatal seizures was significantly associated with epilepsy once other risk factors were controlled in the regression model. Some previous studies have shown an association between neonatal seizures and later epilepsy for cerebral palsy in general. This is the first report of such an association for a single predominant type of cerebral pathology.
Keywords: epilepsy; periventricular leukomalacia; cerebral palsy